Exploring sustainability attitudes in different target groups (Training and Practice : Journal of Educational Sciences, 2020)
In our survey on sustainable living, we aimed to learn about respondents’ knowledge, attitudes, and behaviors about sustainability in six target groups. The areas of the research were the UN 2015 Sustainable Development Goals that can be related to sustainable living. In the framework of this publication, due to space constraints, we only try to present attitudes related to sustainability, we analyze the results of the answers to the related questions.